Regulated street vending as livelihood infrastructure: Reconciling urban order, tourism and economic survival in public space - Sharma, Bishnu (Nepal Public Policy Review, 2025)
Street vending is a crucial livelihood strategy for the urban poor in Nepal, but its governance is often characterized by significant tension. Municipal practices tend to focus on eviction and enforcement efforts to protect public space and right-of-way, viewing vending mainly as an obstacle to urban order. This study examines whether and how street vending can be managed in a way that balances livelihood security with effective public space management in urban and tourism settings. The study employs a qualitative, multi-sourced research design, including a thematic literature and policy review, an analysis of media discourse (2014–2025), and a field study at Narayani Riverside in Bharatpur. This methodology is designed to build a comprehensive, triangulated understanding of street vending as a complex socio-spatial and governance issue. Findings reveal a persistent disconnect between the economic necessity of vending and inconsistent municipal regulation. Vendors demonstrate adaptable spatial practices and contribute to tourism vitality, yet they operate under profound legal insecurity and arbitrary enforcement. A comparative analysis shows this pattern is consistent across the country, although the responses from the local governments range from crackdowns to pragmatic tolerance. Synthesizing this evidence, the study concludes that the current eviction-led approaches are ineffective. It explores a paradigm shift toward planned, participatory regulation as a viable alternative. The research results in a concrete policy framework and an implementation roadmap, proposing mechanisms such as legal recognition, town vending committees, and viability-based zoning. This work provides an evidence-based contribution to the ongoing debate on integrating informal livelihoods into equitable and well-managed urban spaces in Nepal.